Indonesian Capital Market Investor Protection in Cases of Embezzlement - Nefi, Arman; Adiwarman, Adiwarman (Indonesia Law Review, 2023)
Law Number 8 of 1995 on Capital Market, in Articles 90 to 98, regulates fraud, market manipulation and insider trading. There is no regulation of embezzlement in the Indonesian Capital Market. Have the legislators forgotten, or have anticipated that there will never be embezzlement in the legal realm of the Indonesian Capital Market? The paper deals with the absent of criminalization of embezzlement in capital market act and produce the recommendation to cope with the issue. This study uses a normative legal analysis method with a conceptual, an analytical, and a case study approach. Several legal cases that are strongly indicated to be in the realm of embezzlement in the capital market have become the subject of a comprehensive study, with the main characteristic being that the victims are massive, and even more investors suffer losses. Testing through elements of fraud, market manipulation and insider trading did not meet the requirements, however where it is viewed from the elements of the embezzlement, this is more appropriate. However, the Capital Market Law does not have a specific article on embezzlement, which finally direct to Criminal Code with a lighter sanction. Based on such findings and facts, it is necessary to amend the Indonesian Capital Market Law to reach embezzlement.